Proceedings of the 2021 International Conference on Multimedia Retrieval 2021
DOI: 10.1145/3460426.3463626
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Deep Cross-Modal Hashing by Knowledge Distillation for Large-scale Cross-modal Retrieval

Abstract: Cross-modal hashing (CMH) maps heterogeneous multiple modality data into compact binary code to achieve fast and flexible retrieval across different modalities, especially in large-scale retrieval. As the data don't need a lot of manual annotation, unsupervised cross-modal hashing has a wider application prospect than supervised method. However, the existing unsupervised methods are difficult to achieve satisfactory performance due to the lack of credible supervisory information. To solve this problem, inspire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…DGCPN [10] explores intrinsic semantic relationships with graph-neighbor coherence to avoid suboptimal retrieval Hamming space. With introducing knowledge distillation scheme, KDCMH [11] trains an unsupervised method as the teacher model used to provide distillation information to guide supervised method. CMIMH [12] tries to find a balance between reducing the modality gap and losing modality-private information by maximizing mutual information.…”
Section: A Non-continuous Cross-modal Hashingmentioning
confidence: 99%
“…DGCPN [10] explores intrinsic semantic relationships with graph-neighbor coherence to avoid suboptimal retrieval Hamming space. With introducing knowledge distillation scheme, KDCMH [11] trains an unsupervised method as the teacher model used to provide distillation information to guide supervised method. CMIMH [12] tries to find a balance between reducing the modality gap and losing modality-private information by maximizing mutual information.…”
Section: A Non-continuous Cross-modal Hashingmentioning
confidence: 99%
“…4, it can be observed that on both I T and T I, our proposed KGUCH achieves the best performance among the other compared methods in precision-recall curves. CVH (IJCAI 2011) [8] 0.458 0.432 0.410 0.474 0.445 0.419 0.466 0.439 0.415 PDH (ICML 2013) [9] 0.475 0.484 0.480 0.489 0.512 0.507 0.482 0.498 0.494 CMFH (TIP 2016) [25] 0.517 0.550 0.547 0.439 0.416 0.377 0.478 0.483 0.462 CCQ (SIGIR 2016) [26] 0.504 0.505 0.506 0.499 0.496 0.492 0.502 0.501 0.499 CMSSH (CVPR 2010) [15] 0.512 0.470 0.479 0.519 0.498 0.456 0.516 0.484 0.468 SCM (AAAI 2014) [16] 0.517 0.514 0.518 0.518 0.510 0.517 0.518 0.512 0.518 DJSRH (CVPR 2019) [13] 0.513 0.535 0.566 0.546 0.568 0.599 0.530 0.552 0.583 JDSH (SIGIR 2020) [27] 0.554 0.561 0.582 0.582 0.596 0.626 0.568 0.579 0.604 KDCMH (ICMR 2021) [28] 0.615 0.628 0.637 0.623 0.636 0.647 0.619 0.632 0.642 DGCPN (AAAI 2021) [14] 0 CVH (IJCAI 2011) [8] 0.601 0.585 0.576 0.605 0.590 0.583 0.603 0.588 0.580 PDH (ICML 2013) [9] 0.622 0.623 0.619 0.625 0.626 0.629 0.624 0.625 0.624 CMFH (TIP 2016) [25] 0.661 0.658 0.661 0.609 0.604 0.573 0.635 0.631 0.617 CCQ (SIGIR 2016) [26] 0.636 0.638 0.637 0.625 0.626 0.620 0.631 0.632 0.629 CMSSH (CVPR 2010) [15] 0.609 0.604 0.561 0.611 0.605 0.591 0.610 0.605 0.576 SCM (AAAI 2014) [16] 0.636 0.640 0.641 0.661 0.660 0.668 0.649 0.650 0.655 DJSRH (CVPR 2019) [13] 0.666 0.678 0.699 0.683 0.694 0.717 0.675 0.686 0.708 JDSH (SIGIR 2020) [27] 0.669 0.683 0.698 0.686 0.699 0.716 0.678 0.691 0.707 KDCMH (ICMR 2021) [28] 0.713 0.716 0.724 0.711 0.715 0.731 0.712 0.716 0.728 DGCPN (AAAI 2021) [14] 0 [25] 0.163 0.176 0.163 0.495 0.513 0.533 0.329 0.344 0.348 CCQ (SIGIR 2016) [26] 0.235 0.237 0.237 0.400 0.441 0.457 0.317 0.339 0.347 SCM (AAAI 2014) [16] 0.237 0.238 0.238 0.370 0.424 0.437 0.304 0.331 0.338 DJSRH (CVPR 2019) [13] 0.384 0.398 0.406 0.512 0.536 0.544 0.448 0.467 0.475 JDSH (SIGIR 2020) [27] 0.351 0.383 0.399 0.398 0.448 0.480 0.375 0.416 0.440 DGCPN (AAAI 2021) [14] 0 The results are shown in Table 4. Compared to the proposed approach KGUCH with KGUCH-Baseline, constructing a semantic graph in our approach can significantly help promot...…”
mentioning
confidence: 99%